2017
DOI: 10.1186/s12864-017-4032-8
|View full text |Cite
|
Sign up to set email alerts
|

Essential genome of Campylobacter jejuni

Abstract: Background Campylobacter species are a leading cause of bacterial foodborne illness worldwide. Despite the global efforts to curb them, Campylobacter infections have increased continuously in both developed and developing countries. The development of effective strategies to control the infection by this pathogen is warranted. The essential genes of bacteria are the most prominent targets for this purpose. In this study, we used transposon sequencing (Tn-seq) of a genome-saturating library of Tn5 insertion mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…A study on motility defects in C. jejuni has shown that the outcome of a deletion of one gene ( fla B) can be affected by second-site mutations in other genes ( fli W, and flg D) associated with the same phenotype ( de Vries et al, 2015 ). Based on recent studies, genes from the flagellar regulatory cascade were found essential for the fitness of C. jejuni 11168 during an in vitro growth experiment; fli F (MS ring); fli G (C-ring), fli L (motor); flg I and flg A (P-ring); flg B, flg C, flg G and fli E (rod); fli H and fli Q (T3SS); and flg P and prf B_flg (unknown function) ( de Vries et al, 2017 ; Mandal et al, 2017 ). Interestingly, although these genes are required for fitness in colonization of two different hosts, survival in a third host, and invasion of tissue culture cells, no mutations were detected in any of these genes in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…A study on motility defects in C. jejuni has shown that the outcome of a deletion of one gene ( fla B) can be affected by second-site mutations in other genes ( fli W, and flg D) associated with the same phenotype ( de Vries et al, 2015 ). Based on recent studies, genes from the flagellar regulatory cascade were found essential for the fitness of C. jejuni 11168 during an in vitro growth experiment; fli F (MS ring); fli G (C-ring), fli L (motor); flg I and flg A (P-ring); flg B, flg C, flg G and fli E (rod); fli H and fli Q (T3SS); and flg P and prf B_flg (unknown function) ( de Vries et al, 2017 ; Mandal et al, 2017 ). Interestingly, although these genes are required for fitness in colonization of two different hosts, survival in a third host, and invasion of tissue culture cells, no mutations were detected in any of these genes in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Cj1509 could control the expression of selected C. jejuni genes in response to unknown stimuli; however, Cj1509 has been reported to be non-essential in some strains ( de Vries et al, 2017 ). Moreover, in different laboratories, Cj1509 has been shown to be an essential and non-essential gene in the same strain, e.g., C. jejuni 11168 ( Metris et al, 2011 ; de Vries et al, 2017 ; Mandal et al, 2017 ). Thus, it is possible that strain-specific genome content and growth conditions determine the actual role of Cj1509 in C. jejuni physiology.…”
Section: Discussionmentioning
confidence: 99%
“…For the Km R marker strain, we selected 10 mutants randomly from the C . jejuni strain 11168 Tn5 transposon mutant library previously described by Mandal et al [ 56 ] and compared their natural transformation efficiency using genomic DNA of the C . jejuni Cm R marker strain.…”
Section: Methodsmentioning
confidence: 99%